P03.11.A Potential role of pre-radiotherapy MRI for target delineation in high-grade gliomas: a multicenter retro-prospective cohort study. (5th September 2022) - Satragno, C; Gonnelli, A; Cella, E; Scaffidi, C; Ginulla, A; Tagliamento, M; Giannini, N; Gadducci, G; Valenti, S; Grassi, M; Giannelli, F; Bennicelli, E; et al.
Abstract: Background: The optimal timing for target identification in high-grade glioma (HGG) remains unclear due to variability in the hyper-signal T2/FLAIR between MRI performed at diagnosis, post-surgery and at radiotherapy (RT) start. The aim of this study was to retrospectively confirm that RT planned on delayed MRI might allow to spare more normal tissue without decreasing local tumour control, in order to prospectively evaluate the best standard and advanced MRI and metabolic imaging sequences for clinical tumor volume (CTV) adaptation. Material and Methods: We analyzed a retrospective cohort of consecutive patients with HGG treated from 2017 to 2020. All patients had a diagnostic MRI and another performed immediately post-surgery or pre-RT. Target volumes were contoured, based on T2/FLAIR, on diagnostic and post-surgery MRI in group A, while in group B on pre-RT MRI. We analyzed GTV and CTV volume, and the percentage increase between them. Moreover, we compared the two groups in terms of clinical-pathological characteristics and progression-free survival (PFS) and overall survival (OS). A prospective study, started on January 2022, has enrolled patients with HGG evaluated by advanced sequences MRI at diagnosis, post-surgery and pre-RT. In addition, some selected patients have undergone diagnostic DOPA-PET and pre-RT DOPA-PET. 2 MRI-guided contours have been performed for each patient: adapted on T2/FLAIR post-surgery and CTV-adapt on pre-RT, to assess study objectives. Results: In retrospective cohort we analyzed 54 patients (25 group A, 29 group B). The median age of patients was 61 years (IQR 17, 75), 93% had an ECOG PS of 0 or 1, 51 were symptomatic at diagnosis. Patients in group B had more frequently MGMT methylation (59 % vs. 28%, p=0.01) while less frequently frontal lobe involvement (60% vs. 24%, p=0.01). The median percentage increase between GTV and CTV was higher in group A than B: 431% (range 62%-7335%) vs 385% (range 53%-3174%), respectively. No significant difference in the pattern of relapse was observed, since >90% of disease recurrences were in-field in both groups. Median PFS and OS of the overall population were 9.5 months (95% CI 7 - 12) and 18.5 months (95% CI 16 - 24), respectively. Patients in group B had a significant better PFS as compared to those in group A (p=0.03), but similar OS. Nevertheless, imbalance in MTMT methylation status between the two groups was a major driver for PFS. Overall, 37 out of 51 patients had improvement in neurological symptoms (p<0.001), with no difference between the two groups (p=0.54). Conclusion: Our data suggest that CTV adaptation to pre-RT T2/FLAIR may allow reducing RT volume, without affecting symptoms relieving and disease control. Results from the prospective study will help identifying the best adaptation of CTV guided by T2/FLAIR, advanced MRI sequences and metabolic imaging, in order to optimize efficacy and safety of treatment planning.